Converting UML Class Diagrams into Temporal Object Relational DataBase - Ain El Hayat Soumiya; Bahaj Mohamed (Institute of Advanced Engineering and Science, 2017)
Number of active researchers and experts, are engaged to develop and implement new mechanism and features in time varying database management system (TVDBMS), to respond to the recommendation of modern business environment..Time-varying data management has been much taken into consideration with either the attribute or tuple time stamping schema. Our main approach here is to try to offer a better solution to all mentioned limitations of existing works in order to provide the non-procedural data definitions, queries of temporal data as complete as possible technical conversion that allow to easily realize and share all conceptual details of the UML class specifications, from conception and design point of view. This paper contributes to represent a logical design schema by UML class diagrams, which are handled by stereotypes to express a temporal object relational database with attribute timestamping.